2005
DOI: 10.2135/cropsci2005.0085
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and Combining Ability in a Diallel Cross of Ethiopian Mustard Inbred Lines

Abstract: Becker et al., 1999;Miller, 1999). Studies in B. napus, B. rapa, and B. juncea have indicated high levelsHeterosis is commercially exploited in rapeseed (Brassica napus of heterosis. Pradhan et al. (1993) reported 29 to 92% L.) and its potential use has been demonstrated in turnip rape (B. rapa L.) and Indian mustard (B. juncea L.). In Ethiopian mustard heterosis over the best-yielding parents in B. juncea by (B. carinata A. Braun), however, information regarding heterosis has crossing parents of Indian and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
37
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 18 publications
(30 reference statements)
9
37
1
Order By: Relevance
“…of secondary branches per plant. Kumar et al, (1997) and Teklewold and Becker (2005) also reported similar results in Indian mustard with a different set of material. The genotype RH0644 in both the environments for main shoot length and RH0644 in normal environment for siliquae on main shoot with significant desirable gca effects were found to be the good general combiners.…”
Section: Estimation Of General Combining Ability (Gca)mentioning
confidence: 58%
See 2 more Smart Citations
“…of secondary branches per plant. Kumar et al, (1997) and Teklewold and Becker (2005) also reported similar results in Indian mustard with a different set of material. The genotype RH0644 in both the environments for main shoot length and RH0644 in normal environment for siliquae on main shoot with significant desirable gca effects were found to be the good general combiners.…”
Section: Estimation Of General Combining Ability (Gca)mentioning
confidence: 58%
“…Our findings are in agreement with the earlier results in mustard reported by Singh and Murty (1980), Sheikh and Singh (1998) and Chowdhury et al, (2004a).The magnitude of sca effects for seed yield/plant revealed in crosses viz., RH 8814 x RH0555A, RH 0116 x RH0952, BPR 349-9 x RH0644, BPR 349-9 x BPR543-3 and RH0952 x RH0555A in both the environments, seven crosses in normal and late sown environment showed significant positive sca effects. Teklewold et al, (2005), Nassimi et al, (2006) and Wang et al, (1997) observed significant positive sca effect for seed yield. Significant positive sca effects in both the environments were expressed by only one cross combinations, namely, BPR 349-9 x RH0555A for 1000 seed weight, RH0952 x BPR543-3 in normal and RH 8814 x BPR543-3, RH 0116 x BPR 349-9 and RH 0116 x BPR543-3 in late sown environments oil content.…”
Section: Estimation Of Specific Combining Ability (Sca)mentioning
confidence: 95%
See 1 more Smart Citation
“…Likewise, studies with winter cultivars of this species (Amiri-Oghana et al, 2009;Sabaghnia, et al, 2010) showed both additive and dominance gene effects to have a significant role in the inheritance of flowering time. Significant negative GCA and SCA effects were reported for days to flowering (Teklwold .and Becker, 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Studies on combining ability have been done earlier (Kumar et al, 2011;Nasimi et al, 2006;Singh et al, 2010). Various studies on spring cultivars of oilseed rape have shown the important role of GCA and SCA effects for days to flowering and also it be a highly heritable character determined by genes that exhibit some degree of dominance (Teklwold .and Becker, 2005;Hung, et al, 2010;Zhang and Zhu, 2006). Likewise, studies with winter cultivars of this species (Amiri-Oghana et al, 2009;Sabaghnia, et al, 2010) showed both additive and dominance gene effects to have a significant role in the inheritance of flowering time.…”
Section: Introductionmentioning
confidence: 99%